Performance Characteristics of 6.124 MW Solar Power Plant at Military Engineering Service (Jodhpur, Rajasthan): A Case Study - Mahendra Lalwani, Sanjeev Kumar, Atul Soni, Nagendra Kumar Swarnkar (International Journal of Advanced Science and Technology, 2020)
Solar energy is a nonpolluting and the most readily available renewable resource of energy. Photovoltaic (PV) cells can directly convert the sun/solar energy into electricity. This conversion leads to the production of high temperature with focusing collectors for running the steam turbine in a conventional power plant. It delivers a wide range of applications consisting the uniqueness of the solar technologies and converts the mili-watt to megawatt in solar PV. Power generation applications used in the industrial to domestic applications by using solar thermal collectors. This work include the site assessment of Shikargarh Army Area of Jodhpur Rajasthan. Military Engineering Services, Jodhpur implements the project after realizing the overall aspects of solar power potential of Rajasthan This solar PV power Project of the capacity of 6 MW. Depending on the aspects of techno-commercial, their availability, performance under dry/hot climates and maturity level, the most suitable material of PV at selected location is Polycrystalline solar PV technology.